Comparison of Hospitalized COVID-19 Patients in Terms of Disease Course According to the Presence of Gastrointestinal Symptoms Before and After Admission - Kurt, Enes Ali; Bakkaloğlu, Oğuz Kağan; Eşkazan, Tuğçe; Akdoğan, Selma; Önal, Uğur; Candan, Selçuk; Karaali, Rıdvan; Mete, Bilgül; Dikmen, Yalım; Tuncer, Murat; Hatemi, İbrahim; Bal, Kadir (Turkish Journal of Gastroenterology, 2023)
Background: This study aimed to find the prevalence of gastrointestinal symptoms in hospitalized COVID-19 patients and to investigate the effects of gastrointestinal symptoms on the course of the disease during hospitalization.Methods: Patients who were hospitalized due to COVID-19 were included in this retrospective study. The diagnostic method of COVID-19 was either a positive reverse transcription polymerase chain reaction test or a typical finding in chest computed tomography. This study was conducted by contacting patients by phone 1 month after they were discharged from hospital to investigate gastrointestinal symptoms. Patients’ laboratory findings at the time of admission, medications they used, and clinical findings were obtained from hospital records retrospectively. Patients with gastrointestinal symptoms were divided into 2 groups according to the start of treatment: pre-treatment and post-treatment groups.Results: At least 1 gastrointestinal symptom (anorexia, weight loss, diarrhea, nausea, vomiting, and abdominal pain) was present in 67.5% of 435 patients (55.6% male, mean age 52.8). If anorexia and weight loss are excluded, the rate of the presence of at least 1 gastrointestinal symptom is 54%. Gastrointestinal symptoms were present in 48.9% before the initiation of COVID-19 treatment. The most prevalent 3 symptoms were anorexia, weight loss, and diarrhea (56%, 52%, and 35.6%, respectively). Presence of pre-treatment gastrointestinal symptoms was associated with elevated C-reactive protein levels. Pre-treatment gastrointestinal symptoms were more common in those who received oxygen supply and who were intubated. Resolution of gastrointestinal symptoms takes longer time in those who were admitted to intensive care unit. Weight loss and diarrhea were more common in COVID-19 patients with gastrointestinal symptoms who were intubated than who were not intubated. Abdominal pain was not found to be a significant predictor of disease severity.Conclusion: The prevalence of at least 1 gastrointestinal symptom in hospitalized COVID-19 patients was 67%. The most prevalent symptoms were anorexia, weight loss, and diarrhea. Presence of pre-treatment gastrointestinal symptoms was associated with elevated C-reactive protein levels, use of oxygen supply, and intubation. Gastrointestinal symptoms persist longer in those admitted to intensive care unit.Cite this article as: Kurt EA, Bakkaloğlu OK, Eşkazan T, et al. Comparison of hospitalized COVID-19 patients in terms of disease course according to the presence of gastrointestinal symptoms before and after admission. Turk J Gastroenterol. 2023;34(4):322-331.